Effects of feeding chicken egg yolk antibodies on intestinal cell apoptosis, oxidative stress and microbial flora of tilapia (Oreochromis niloticus) infected with Streptococcus agalactiae - Zhang, Linpeng; Bai, Yanhan; Tao, Junjie; Yang, Shiyi; Tu, Chengming; Liu, Lihan; Huang, Xiaoman; Li, Lin; Qin, Zhendong (Fish & shellfish immunology, 2024)
Streptococcosis, the most common bacterial disease of fish in recent years, is highly infectious and lethal, and has become an important factor hindering the healthy and sustainable development of aquaculture. Chicken egg yolk antibody (IgY) has the advantages of high antigen specificity, inexpensive and easy to obtain, simple preparation, no toxic side effects, and in line with animal welfare, which is a green and safe alternative to antibiotics. In this study, the potential of specific IgY in the treatment of gastrointestinal pathogens was explored by observing the effects of specific IgY on intestinal flora, pathological tissue, apoptosis, oxidative stress, and inflammatory response of tilapia. We used the specific IgY prepared in the early stage to feed tilapia for 10 days, and then the tilapia was challenged with Streptococcus agalactiae. The results showed that feeding IgY before challenge had a small effect on the intestinal flora, and after challenge specific IgY decreased the proportion of Streptococcus and increased the diversity of the intestinal flora; in histopathology, specific IgY decreased tissue damage and maintained the integrity of tissue structure. Further study found that specific IgY can reduce intestinal epithelial cell apoptosis and reduce caspase activity; at the same time, the content of MDA was decreased, and the activities of SOD, CAT, GSH-Px and GR were increased. In addition, specific IgY can down-regulate the expression levels of IL-8 and TNF-α genes and up-regulate the expression levels of IL-10 and TGF-β. The results of this study showed that specific IgY could improve the intestinal flora of tilapia infected with Streptococcus agalactiae, reduce intestinal cell apoptosis, oxidative stress injury and inflammatory response, thereby reducing tissue damage and protecting the health of tilapia. Overall, specific IgY can be further explored as a potential antibiotic alternative for gastrointestinal pathogen infections. •Specific IgY decreased the proportion of Streptococcus and increased the diversity of the intestinal flora.•Specific IgY decreased tissue damage and maintained the integrity of tissue structure.•Specific IgY reduced caspase activity and reduced intestinal cell apoptosis.•IgY reduced oxidative stress injury and inflammatory response in intestinal.